Equal Area Laws and Latent Heat for d-Dimensional RN-AdS Black Hole. (19th November 2014) - Zhang, Li-Chun; Zhao, Hui-Hua; Zhao, Ren; Ma, Meng-Sen
Abstract : We study the equal area laws of d -dimensional RN-AdS black hole. We choose two kinds of phase diagrams, P - V and T - S . We employ the equal area laws to find an isobar which is the real two-phase coexistence line. Our calculation is much simpler to derive the critical value of the thermodynamic quantities. According to the thermodynamic quantities, we also study the latent heat of the black hole.